From exclusion to excellence: practical aspects of inclusion and the role of the teacher in inclusive education - Deli, Kitti (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book review: Michal Razer és Victor J. Friedman (2017): From Exclusion to Excellence: Building Restorative Relationships to Create Inclusive Schools. IBE on Curriculum, Learning, and Assessment Volume 1.The Netherlands, Sense Publishers.